Anti-pneumococcal surface protein A antibodies transferred from maternal mice protect offspring against lethal infection with Streptococcus pneumoniae serotype 3 - Eisuke Kuroda; Eisuke Kuroda; Yuriko Tanaka; Yuriko Tanaka; Shigeto Hamaguchi; Shigeto Hamaguchi; Shigeto Hamaguchi; Shigeto Hamaguchi; Shigeto Hamaguchi (Frontiers in Bacteriology)
Streptococcus pneumoniae (S. pneumoniae) causes otitis media, pneumonia, and invasive pneumococcal diseases (IPDs) such as meningitis and septicemia in humans. IPDs are fatal in children and can cause irreversible sequelae such as brain damage and impaired hearing. The introduction of 7- and 13-valent pneumococcal, conjugate, polysaccharide-based vaccines (PCV7, Prevnar 7®; and PCV13, Prevnar 13®) has decreased pediatric IPD infections. However, PCV13 provides limited protection against S. pneumoniae serotype 3. A new candidate pneumococcal vaccine antigen, pneumococcal surface protein A (PspA), which is found in almost all S. pneumoniae serotypes, addresses the drawbacks of CPS-based vaccines. In a previous study, the PspA3 + 2 protein was developed as a broad-spectrum vaccine candidate that combines PspA clades 2 and 3. We assessed whether vaccinating pregnant mice with PspA3 + 2 would transfer anti-PspA3 + 2 antibodies to pups, and if so, whether the transferred antibodies would protect against bacteremia caused by S. pneumoniae serotype 3. A PspA3 + 2 vaccine containing aluminum hydroxide gel (alum) and cytosine-phosphate-guanosine oligodeoxynucleotide K3 adjuvants induced anti-PspA antibodies in adult female mice, and an enzyme-linked immunosorbent assay revealed anti-PspA antibodies in serum samples from their offspring. Survival rates after lethal infection with S. pneumoniae serotype 3 were significantly higher among these neonates than in negative controls. These findings suggest that anti-PspA3 + 2 antibodies transferred from maternal mice vaccinated with PspA3 + 2 protect against bacteremia caused by S. pneumoniae serotype 3 in newborn pups.